186k views
3 votes
3(c-1)+2(3c+1)=-(3c+1)

User Compito
by
6.5k points

2 Answers

4 votes

Answer:

Explanation:

3c-3+6c+2= -3c-1 ( 3c+6c =9c) and (-3+2 = -1) so

9c -1 = -3c-1 = so add 3c to both sides to get rid of the 3c on the right side

9c-1 +3c = -3c +3c -1 =

12c-1 = -1 add +1 to both sides

12c-1 +1 = -1 +1

12c=0

c = 0/12

so c= 0

User SuperNano
by
5.7k points
1 vote

Answer:

c=0

Explanation:

3(c-1)+2(3c+1)=-(3c+1)

Distribute

3c -3 +6c +2 = -3c -1

Combine like terms

9c -1 = -3c -1

Add 1 to each side

9c = -3c

Add 3c to each side

12c = 0

Divide by 12

c = 0

User Guus Geurkink
by
5.5k points